Pembinaan Kreativitas Dan Potensi Seni Masyarakat Desa BanjarAgung Udik Melalui Teknik Ecoprint - Nuning Nurcahyani; Primasari Pertiwi; Kusuma Handayani; Gina Dania Pratami (CV. Multi Kreasi Media, 2025)
This activity was carried out in Banjar Agung Udik Village, Pugung District, Tanggamus Regency. The diversity of flora in Banjar Agung Udik Village creates great potential for the development of nature-based art and creativity. The use of natural materials for art and creativity will not only produce unique and aesthetic works of art, but also have high economic potential. One method that can be used is the ecoprint technique, so a deep understanding of the ecoprint technique, research on appropriate natural materials, and training for the local community are needed. The PKM activity was carried out in 2 stages, the first stage was the delivery of material through lectures and discussions, the second stage was a demonstration/practice of making patterned cloth with the ecoprint technique. The evaluation results showed an increase in the pre-test and post- test scores of 2.75 or 13.75%. The conclusion of this activity is that the knowledge, insight, and skills of the community in Banjar Agung Udik Village have increased, especially regarding the use of the ecoprint technique in making patterned cloth.